A REVIEW OF RESEARCH ON THE RELATIONSHIPS BETWEEN READING FLUENCY AND EYE MOVEMENTS AMONG STUDENTS - Soh, Or-Kan (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents a systematic literature review of literature on eye-tracking and reading tasks by using 20 studies in total from abroad and local, which were published between 2015 and 2019. This paper aims at scrutinizing trends and gaps based on the observation from the literature regarding the usage of eye- tracking devices in examining the relation between eye movements and reading fluency. Six main findings emerged: (a) there is a fairly constant interest in trend for incorporating eye-tracking in measuring eye movements during reading; (b) inefficiency to generalize to real-word reading tasks; (c) there is a scant studies on population from diverse backgrounds; (d) the relation between eye movement patterns and underlying cognitive processes is scarcely reported; (e) there is a scarce of eye-tracking studies conducted locally. These findings were analyzed to determine the the implications on the research development of eye-tracking towards reading fluency.